Effect of Social Media on Consumer Buying Behavior in the Electronics Market - Dangol, Riddhi; Bhatta, Ritika; Pokharel, Sulabhi; Shrestha, Zenith; Sah, Amit; Thakur, Ritesh Kumar (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.009This research examines the effect of social media on consumer buying behavior in the electronics market in Kathmandu, Nepal. A survey was conducted on 151 social media users to analyze the influence of psychographic factors, advertising strategies, social media engagement metrics, and influence of social media influencers and celebrities. Descriptive statistics, correlation, ANOVA, and linear regression were employed for data analysis. In line with prior studies, it has indicated that consumer buying behavior can be influenced by focusing on psychographic factors, advertising strategies, social media engagement metrics, and the influence of social media influencers and celebrities. In addition to these results suggest that social media plays a crucial role in shaping consumer electronics purchasing decisions, with user reviews, ratings, and influencer recommendations holding more weight than traditional marketing methods.